Impact of instant visual guidance via video technology on the correction of some offensive skills performance errors in basketball - Hassan, M. M.; Khalaf, H. H.; Mosleh, O. A. (Asian Journal of Sports Medicine, 2023)
Background: Various methods of instructional feedback, whether provided before, during, or immediately after performance, come in different forms, such as verbal communication, educational booklets, and video technology. Choosing the most suitable feedback method is crucial to help learners pinpoint specific motion segments contributing to errors.